Anisotropic coating of a-plane oriented hydroxyapatite via a drop-on-demand micro-dispensing technique. (14th October 2020) - Konishi, Toshiisa; Lye, Yun Min; Qiu, Xihe; Lim, Poon Nian; Thian, Eng San
Abstract: Bone and tooth enamel surface are made up of different crystallographically hydroxyapatite (HA), whereby bone comprises a ( b )-planes of HA whilst tooth enamel comprises c -planes of HA. The reason behind the difference between HA orientations in both tissues are still yet to be discovered. We report the fabrication of anisotropic coatings of a -plane oriented HA according to the following process: (i) synthesis of a -plane oriented HA powders via a hydrothermal reaction and (ii) fabrication of a -plane oriented HA coatings via a Drop-on-Demand (DoD) micro-dispensing technique. Two types of HAs with high a -plane orientation degree of 72.2 and 75.6% (HA10 and HA84, respectively) was synthesised for the DoD coatings. The HA84 coating demonstrated more uniform and flatter surface than HA10 coating. The heat treatment of HA10 and HA84 coatings prepared with mesh-sieved particles led to a low adhesion strength for the substrates. However, the orientation degrees of those coatings (96.0 and 94.6%, respectively) were higher than the coatings without mesh-sieving.